Intelligence and the function of government - Baldino, Daniel; Crawley, Rhys (MUP Academic. Defence series., 2018)
Intelligence plays an important, albeit often hidden hand, in the everyday function of government. Australia's intelligence agencies, collectively referred to as the Australian Intelligence Community (AIC), are an established and fundamental component of the bureaucracy. Their aim is to provide the government with 'information' to better enable it to tackle the issues confronting it, to be better armed, informed and forewarned of what might lay ahead and to facilitate coherent policy-making. This book draws on a wide range experts including academics, former and current strategic advisers and members of government, private industry professionals and intelligence community experts, to provide a diagnostic, clear-eyed approach in explaining, accessing and exposing the central foundations and frameworks necessary for effective practice of intelligence in Australia, as well as the shaping of intelligence expectations.